The birds - Peterson, Roger Tory, 1908- (Alexandria, Va. : Time-Life Books, 1978)
Traces the evolution of birds and discusses the varied sizes, shapes , colors, and habits of some representatives of the over 9,000 species existing today.
Includes bibliographical references (p. 186) and index
Keywords: Birds